2015
DOI: 10.5751/es-07522-200217
|View full text |Cite
|
Sign up to set email alerts
|

Managing for climate change on federal lands of the western United States: perceived usefulness of climate science, effectiveness of adaptation strategies, and barriers to implementation

Abstract: ABSTRACT. Recent mandates in the United States require federal agencies to incorporate climate change science into land management planning efforts. These mandates target possible adaptation and mitigation strategies. However, the degree to which climate change is actively being considered in agency planning and management decisions is largely unknown. We explored the usefulness of climate change science for federal resource managers, focusing on the efficacy of potential adaptation strategies and barriers lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 34 publications
(60 reference statements)
2
73
0
Order By: Relevance
“…While research partnerships exist between some universities and PAs in Madagascar, the lack of communication between researchers and local PA managers means that valuable data and information rarely ends up informing actual PA management (Rafidimanantsoa et al, 2018). Involving managers in research design means that findings are more likely to be relevant and used to improve management (Dilling & Lemos, 2011;Kemp et al, 2015) and we argue that methods for the co-production and exchange of knowledge between researchers, managers, and local communities offer a way to better address the complexities of PAs and their management for both beneficiaries and managers (Bouska, Lindner, Paukert, & Jacobson, 2016;Colloff et al, 2017;Gardner, 2012;Reyers et al, 2010). This echoes similar recommendations from other recent studies investigating drivers behind the "research-implementation" gap (Cvitanovic, Hobday, van Kerkhoff, & Marshall, 2015;Gossa, Fisher, & Milner-Gulland, 2015;McNie, 2007;Toomey, Knight, & Barlow, 2017;Walsh, Dicks, & Sutherland, 2015).…”
Section: Potential For Coproduction Of Knowledge Between Researchermentioning
confidence: 99%
“…While research partnerships exist between some universities and PAs in Madagascar, the lack of communication between researchers and local PA managers means that valuable data and information rarely ends up informing actual PA management (Rafidimanantsoa et al, 2018). Involving managers in research design means that findings are more likely to be relevant and used to improve management (Dilling & Lemos, 2011;Kemp et al, 2015) and we argue that methods for the co-production and exchange of knowledge between researchers, managers, and local communities offer a way to better address the complexities of PAs and their management for both beneficiaries and managers (Bouska, Lindner, Paukert, & Jacobson, 2016;Colloff et al, 2017;Gardner, 2012;Reyers et al, 2010). This echoes similar recommendations from other recent studies investigating drivers behind the "research-implementation" gap (Cvitanovic, Hobday, van Kerkhoff, & Marshall, 2015;Gossa, Fisher, & Milner-Gulland, 2015;McNie, 2007;Toomey, Knight, & Barlow, 2017;Walsh, Dicks, & Sutherland, 2015).…”
Section: Potential For Coproduction Of Knowledge Between Researchermentioning
confidence: 99%
“…Kemp et al (2015) found that federal agencies tasked with incorporating climate chance science into management of public lands were faced with similar limitations. Similarly, lack of information at relevant scales and budget constraints were the most limiting constraints for federal public land managers to adapt to climate change in mountainous Colorado (Archie et al 2014).…”
Section: Follow-up Surveymentioning
confidence: 99%
“…Although resource limitations of time and funding are often controlled by forces outside the realm of influence of individual managers and scientists, disconnections between research and management communities is a constraint that both resource managers and scientists can work to remove through regular communication and collaboration. The U.S. Forest Service has attempted to overcome this obstacle through the creation of climate change coordinator positions (Kemp et al 2015) and science-management partnerships (Littell et al 2012). The participating managers in our workshop were eager to help scientists understand the difficulties inherent to managing floodplains, and to aid in the identification of science products that meet their needs, suggesting partnerships between managers and researchers can identify science needs, specify relevant temporal and spatial scales, and determine user-friendly product formats.…”
Section: Follow-up Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Dry forests of Western North America face increasingly extensive, frequent, and severe disturbances from insects, disease, and wildfire due to growing climatic and anthropogenic pressures [1][2][3]. These disturbances can have large social and financial implications for the communities that are reliant on the resources and ecological benefits provided by these systems [4].…”
Section: Introductionmentioning
confidence: 99%